Produção e caracterização de filmes de carbeto de silício amorfo hidrogenado o (a-SiC:H) depositados por plasma à partir de precursores líquidos sobre liga de titânio (Ti-6Al-4V) - Nass, Karina Carvalho de Farias [UNIFESP] (2015)
The hydrogenated amorphous silicon carbide (a-SiC:H) shows several features that make it desirable for thibological application. Among them are high hardness, low friction coefficient, high corrosion resistance and high temperature resistance, qualify it for use in strategic areas of pharmaceutical, biomedical, microelectronics and many others. In this work a-SiC:H films was produced on the titanium alloy (Ti-6Al-4V) to obtain films with high adhesion and high tribological performance with high performance tribological and high adhesion to the substrate. The film was deposited using Plasma Enhanced Chemical Vapor Deposition (PECVD) from from liquid precursors of silicon, carbon and hydrogen, such a hexamethyldisiloxane (HMDSO), [Si (CH3)3]2O and tetramethylsilane (TMS) Si(CH3)4 . The deposition temperature range from 400 to 600 °C for both precursors. To verify the effect on the tribological properties of the addition of methane in the film deposition was performed gas mix of hexamethyldisiloxane with metane (CH4) at temperature of 600 °C. The FT-IR, X Rays, Raman and EDS was used to verify the presence of a-SiC:H and also the crystallinit of the films. The mechanic and tribology characteristics were evaluated through scratching test, friction and wear. Surface perfilometer was used to obtain the thickness and optical perfilometer to obtain the topography of the samples. The HMDSO films at 500 °C (H5) and HMDSO/CH4 at 600 °C (HM6) showed the higher deposition rate values, critical load range and worn volume of the sphere, which suggests that these films have a higher hardness and adhesion. Otherwise in friction analysis the H5 film obtained less friction coefficient value, which is 0.102 versus 0.199 to HM6.